The orphan of Ellis Island : A time-travel adventure - Woodruff, Elvira 1951- (New York : Scholastic, 2000)
During a school trip to Ellis Island, Dominick Avaro, a ten-year-old foster child, travels back in time to 1908 Italy and accompanies two young emigrants to America.
M
b
b
Keywords: timetravel; orphan; immigrant; Italy